Laminoplasty Does not Lead to Worsening Axial Neck Pain in the Properly Selected Patient With Cervical Myelopathy: A Comparison With Laminectomy and Fusion. Issue 24 (15th December 2017) - Stephens, Byron F.; Rhee, John M.; Neustein, Thomas M.; Arceo, Rafael
Abstract : Study Design: Retrospective cohort study of prospectively collected data. Objective: To determine if laminoplasty (LP) is associated with worsening axial neck pain in patients with multilevel cervical myelopathy, and to compare neck pain, clinical outcomes, and radiographic measures in a group undergoing laminectomy and fusion (LF). Summary of Background Data: Postoperative new or worsening axial neck pain is commonly cited as a major disadvantage of laminoplasty. However, there remains a paucity of corroborative data from large series. Methods: Following institutional review board approval, we reviewed the medical records, radiographs, and prospective clinical outcomes database of 85 patients undergoing LP and 52 patients undergoing LF for cervical myelopathy with minimum 1-year radiographic follow-up and average clinical follow-up of 18.5 months. LP was performed in those with neutral to lordotic C2–7 alignment and who did not complain of diffuse axial pain. Otherwise, LF was performed. Clinical outcomes included visual analogue score (VAS)-neck pain, VAS-total pain, neck disability index (NDI), short form 36, modified Japanese Orthopaedic Association (mJOA), and several radiographic parameters. Results: VAS-neck did not worsen in LP (−0.2, P  = 0.54) and did improve in LF (−2.0, P  = 0.0013). VAS-total improved significantly in both groups (LF −1.04 ± 0.52, P  = 0.05; LP −1.4 ± 0.51, P  = 0.008). NDI improved in both groups, but was significant in only LP (LP decreased 6.79 ± 2.25, P  = 0.0032; LF decreased 4.01 ± 3.05, P  = 0.19). mJOA scores improved significantly in both groups (LP improved 2.89 ± 0.27, P  < 0.0001; LF improved 2.45 ± 0.33, P  < 0.0001). There was a small loss of cervical lordosis in both groups that was significant in LP (LP 2.92° loss, P  = 0.0181; LF 1.25° loss, P  = 0.53). Conclusion: In a carefully selected group of myelopathic patients without significant diffuse axial pain preoperatively and appropriate sagittal alignment, laminoplasty did not lead to worsening axial neck pain, and it was associated with significant improvements in other clinical and myelopathy outcomes. Although laminoplasty is not indicated in every myelopathic patient, this study exemplifies its efficacy as a non-fusion operation in the appropriately selected patient and assuages concerns regarding worsening axial neck pain in such patients following surgery. Level of Evidence: 3